2021
DOI: 10.37486/2675-1305.ec03018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Culex flavivirus (Flaviviridae) from a natural Culex (Culex) chidesteri Dyar, 1921 population, Caatinga Biome, Semiarid Scrubland, Brazil

Abstract: The first detection of Culex flavivirus (CxFV) in mosquitoes was described in 2007 in Japan and subsequently in different areas of the Americas, Africa, and Asia. In this study, we report the identification of CxFV in Culex (Culex) chidesteri Dyar, 1921 mosquitoes collected in the Açu National Forest - FLONA/ AÇU-RN, a preserved area of Biome Caatinga, State of Rio Grande do Norte, Brazil. We performed nucleotide-sequencing analysis in order to compare with other previously identified CxFV collected from aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In 2013, Culex quinquefasciatus Say, 1823 mosquitoes positive for CxFV were detected in the Midwest in Cuiabá [ 15 ]. Between 2011 and 2013, Culex chidesteri Dyar, 1921 infected were found in the Northeast, in the State of Rio Grande do Norte [ 16 ]. A study published in 2018 reported a high prevalence of insect-specific Flaviviruses in Culex spp.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Culex quinquefasciatus Say, 1823 mosquitoes positive for CxFV were detected in the Midwest in Cuiabá [ 15 ]. Between 2011 and 2013, Culex chidesteri Dyar, 1921 infected were found in the Northeast, in the State of Rio Grande do Norte [ 16 ]. A study published in 2018 reported a high prevalence of insect-specific Flaviviruses in Culex spp.…”
Section: Introductionmentioning
confidence: 99%